Christina Higgins. 2009. English as a Local Language - Lusekelo, Amani (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Christina Higgins credibly presents the situation of English in East Africa as scrutinized from four areas, which she investigated in the field: the newspaper journalism, annual beauty pageants for young women, the hip hop music of the youth, and advertisements. For me, as a Tanzanian, it has been a pleasure to review a book that illuminatingly documents the language situation, the cultural conceptualization and the localization of English that is taking place in the multilingual society in Tanzania.